A Comparative Analysis of Startup Valuation Using the Dave Berkus and Scorecard Methods: A Case Study of TSDC Store - I Made Dwika Priandana; I Gede Juliana Eka Putra; I Made Dwi Hi ta Darmawan (Riviera Publishing, 2026)
TSDC (Tanda Sayang dan Cinta) Store is a startup in the handicraft sector that is currently in the growth phase. To support business development and attract funding from investors, an accurate startup valuation assessment is required. This research aims to analyze and compare the valuation of the TSDC Store startup using the Dave Berkus Method and the Scorecard Method, with a focus on non-financial factors. This study employs a quantitative descriptive approach, with data obtained through interviews and documentation. The analysis focuses on non-financial factors, including the strength of the business idea, product readiness (prototype), management team quality, strategic relationships, and launch and sales strategies. The results indicate that the valuation of TSDC Store using the Dave Berkus Method is IDR 3,900,000,000, whereas the valuation using the Scorecard Method is IDR 2,306,250,000. The difference in valuation arises from the distinct assessment approaches: the Dave Berkus Method emphasizes the internal potential of the startup, while the Scorecard Method compares the startup with similar ventures in the market. Both valuation methods suggest that TSDC Store has strong growth potential, as the estimated values exceed the stage-based valuation threshold of IDR 500,000,000..